1994
DOI: 10.2527/1994.72123246x
|View full text |Cite
|
Sign up to set email alerts
|

Wet corn distillers byproducts compared with dried corn distillers grains with solubles as a source of protein and energy for ruminants

Abstract: Five trials investigated the feeding value of wet and dried corn distillers byproducts as a source of protein and energy for growing and finishing cattle and investigated the effect of heat damage on the feeding value of dried distillers byproducts. In a calf growth trial, no differences in rate of gain or protein efficiency were observed among calves fed wet distillers byproducts (wet distillers grains + thin stillage; WDB) or one of three composites of dried distillers grain + solubles (DDGS) having a low, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
208
13
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(263 citation statements)
references
References 28 publications
(24 reference statements)
35
208
13
7
Order By: Relevance
“…Modification of beef SR membrane fatty acid profiles by feeding WDGS likely occurred by the same mechanism that modification of beef muscle fatty acid profiles occurs. Although the majority of the unsaturated fatty acids in the diet were biohydrogenated to saturated fatty acid (SFA) by the rumen microflora, WDGS has double the amount of corn oil (Ham et al 1994) compared with corn, which led to greater deposition of 18 : 2 and PUFA in the (Wood et al 2008;Smith et al 2006). Perhaps, the 0% WDGS steers needed to generate more MUFA from SFA because less PUFA was available in the plasma to incorporate in the organelle membrane.…”
Section: Sr Membrane Fatty Acidsmentioning
confidence: 99%
“…Modification of beef SR membrane fatty acid profiles by feeding WDGS likely occurred by the same mechanism that modification of beef muscle fatty acid profiles occurs. Although the majority of the unsaturated fatty acids in the diet were biohydrogenated to saturated fatty acid (SFA) by the rumen microflora, WDGS has double the amount of corn oil (Ham et al 1994) compared with corn, which led to greater deposition of 18 : 2 and PUFA in the (Wood et al 2008;Smith et al 2006). Perhaps, the 0% WDGS steers needed to generate more MUFA from SFA because less PUFA was available in the plasma to incorporate in the organelle membrane.…”
Section: Sr Membrane Fatty Acidsmentioning
confidence: 99%
“…Rumen undegraded CP (RUP) was calculated as the ratio of residual CP from the 12-h rumen incubation to the original CP (Ham et al 1994). Post-ruminal availability of RUP was determined following the in vitro three-step procedure of Calsamiglia and Stern (1995).…”
mentioning
confidence: 99%
“…Towards the end of the growing phase, ADG, G/F ratio and rumen pH were similar, while DMI decreased among calves fed MSD diet compared to MS. Ham et al (1994) reported that inclusion of 20 % wet corn distillers' grain plus soluble matter or DDGS in a dry-rolled-maizebased feed increased DMI and ADG in crossbred beef calves of similar body weight. Buckner et al (2007) also reported an improved grow thin finishing steers when 20 % of the feed was replaced with DDGS.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to whole barley, maize has been found to improve growth performance and feed digestibility in grainfed calves (Noon et al, 1998;Ham et al, 1994) found that replacing dry-rolled maize with up to 40 % DDGS reduced acidosis and improved growth performance in steers. Similar results were found by Buckner et al (2007), who obtained the greatest improvement when dry-rolled maize was replaced with 20 % DDGS in comparison with rolled barley and canola meal.…”
mentioning
confidence: 99%